2022
DOI: 10.1371/journal.ppat.1010771
|View full text |Cite
|
Sign up to set email alerts
|

The ESX-4 substrates, EsxU and EsxT, modulate Mycobacterium abscessus fitness

Abstract: ESX type VII secretion systems are complex secretion machineries spanning across the mycobacterial membrane and play an important role in pathogenicity, nutrient uptake and conjugation. We previously reported the role of ESX-4 in modulating Mycobacterium abscessus intracellular survival. The loss of EccB4 was associated with limited secretion of two effector proteins belonging to the WXG-100 family, EsxU and EsxT, and encoded by the esx-4 locus. This prompted us to investigate the function of M. abscessus EsxU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The effects of ESX-4 are known to be substrate dependent since deletion of ESX-4 core complex genes results in lower expression of EsxU and EsxT (ESX-4 substrates) as well as PE-PPE proteins (ESX-3 substrates) [4]. In line with these findings, a recent study shows that EsxU and EsxT from M. abscessus form a heterodimer involved in phagosome membrane damage of macrophages [65]. Therefore, the EsxU/EsxT pair is crucial for inducing membrane permeability, which is advantageous during early stages of bacterial infection.…”
Section: Secretion Systems In M Abscessusmentioning
confidence: 71%
See 2 more Smart Citations
“…The effects of ESX-4 are known to be substrate dependent since deletion of ESX-4 core complex genes results in lower expression of EsxU and EsxT (ESX-4 substrates) as well as PE-PPE proteins (ESX-3 substrates) [4]. In line with these findings, a recent study shows that EsxU and EsxT from M. abscessus form a heterodimer involved in phagosome membrane damage of macrophages [65]. Therefore, the EsxU/EsxT pair is crucial for inducing membrane permeability, which is advantageous during early stages of bacterial infection.…”
Section: Secretion Systems In M Abscessusmentioning
confidence: 71%
“…In line with these findings, a recent study shows that EsxU and EsxT from M . abscessus form a heterodimer involved in phagosome membrane damage of macrophages [ 65 ]. Therefore, the EsxU/EsxT pair is crucial for inducing membrane permeability, which is advantageous during early stages of bacterial infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that EsxUT is the primary secretion substrate of ESX-4, but previous studies in Mtb and M. smegmatis have only examined esxUT gene expression through sigma factor overexpression ( 57 , 58 ) and esxUT gene transcript levels in the context of mycobacterial distributive conjugal transfer ( 34 , 44 ). While EsxUT secretion has been observed in M. abscessus ( Mab ), it should be noted that the Mab EsxT homolog contains the H xxxD/Exx h xxx H motif necessary for secretion ( 59 ). To surmise, we do not actually know if EsxUT is secreted in Mtb , which may explain why EsxUT was not detected in our proteomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This initially suggested that part of the explanation for the increased virulence could be increased ESX-4 activity. However, a recent paper found that specific deletion of the secretion substrates alone ( esxU and esxT ) caused a hypervirulent phenotype in mice, suggesting the role of ESX-4 in virulence is complex and still poorly understood [ 85 ]. The exact interplay, therefore, of B11, ESX-4 as a whole, specifically the ESX-4 secretion substrates and bacterial virulence should continue to be a focus of intense research.…”
Section: Discussionmentioning
confidence: 99%